Linkage among genes responsible for fumonisin biosynthesis in Gibberella fujikuroi mating population A. - Desjardins, A E (1996)
Most naturally occurring strains of the fungus Gibberella fujikuroi mating population A produce high levels of the mycotoxin fumonisin B1 (FB1), which is oxygenated at both carbons C-5 and C-10. Some strains, however, produce only FB2 or FB3, suggesting that they lack the ability to hydroxylate position C-10 or C-5, respectively. Genetic analysis indicates that these different phenotypes are due to single gene defects at closely linked loci designated fum2 and fum3. Further allellism tests indicate that both fum2 and fum3 are closely linked to fum1, a previously identified gene that regulates fumonisin production. The recovery frequency of FB1-producing progency from cross 510 between fum1 and fum2 mutations suggests a map distance of approximately 6.2 cM between these two loci. Amplified fragment length polymorphism analysis of parents and progeny of cross 510 was employed to confirm that the FB1-producing strains are recombinant progeny. We conclude that fum1, fum2, and fum3 constitute a fumonisin biosynthetic gene cluster on chromosome 1 of the restriction fragment length-map of G. fujikuroi.